The Rationale Driving the Evolution of Deep Brain Stimulation to Constant‐Current Devices. Issue 2 (29th August 2014) - Bronstein, Jeff M.; Tagliati, Michele; McIntyre, Cameron; Chen, Robert; Cheung, Tyler; Hargreaves, Eric L.; Israel, Zvi; Moffitt, Michael; Montgomery, Erwin B.; Stypulkowski, Paul; Shils, Jay; Denison, Timothy; et al.
<x xml:space="preserve">Abstract</x> Objective Deep brain stimulation (DBS) is an effective therapy for the treatment of a number of movement and neuropsychiatric disorders. The effectiveness of DBS is dependent on the density and location of stimulation in a given brain area. Adjustments are made to optimize clinical benefits and minimize side effects. Until recently, clinicians would adjust DBS settings using a voltage mode, where the delivered voltage remained constant. More recently, a constant‐current mode has become available where the programmer sets the current and the stimulator automatically adjusts the voltage as impedance changes. Methods We held an expert consensus meeting to evaluate the current state of the literature and field on constant‐current mode versus voltage mode in clinical brain‐related applications. Results/Conclusions There has been little reporting of the use of constant‐current DBS devices in movement and neuropsychiatric disorders. However, as impedance varies considerably between patients and over time, it makes sense that all new devices will likely use constant current.